Daily field checking list by Walter Rosene, April 2, 1933 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated April 2, 1933. This checklist was used by Walter Rosene to record birds sighted around Long Pond, Yale Slough and Rippey Slough with Bob Walker and George Hendrickson between 8:00 and 4:00. Plustek--flatbed